PENGARUH MODEL PEMBELAJARAN KOOPERATIF LEARNING TIPE JIGSAW TERHADAP HASIL BELAJAR SISWA DALAM MATA PELAJARAN IPS KELAS V SD NEGERI SUDIRMAN IV MAKASSAR - Rahmiati; Nurdin; Syamsuriyanti (STKIP Subang, 2025)
This research is a pre-experimental research conducted on fifth grade students of SD Negeri Sudirman IV Makassar. The purpose of this research is to determine whether there is an Influence of the Jigsaw Cooperative Learning Model on Student Learning Outcomes in the Fifth Grade Social Studies Subject of SD Negeri Sudirman IV Makassar. This research is a quantitative research with a population of all fifth grade students and the sample is 23 fifth grade students of SD Negeri Sudirman IV Makassar. The data found in this study were analyzed using descriptive statistical analysis techniques using the t-test formula. The research instruments used were learning outcome tests and observation guidelines. The results of the analysis of the social studies learning outcome test data show that the level of ability of grade V students of SD Negeri Sudirman IV Makassar before the implementation of the jigsaw cooperative learning model is categorized as low with a percentage of 30.43% very low, 30.43% low, 13.04 medium, 21.74 high and 4.36% very high. Learning outcomes after the implementation of the jigsaw cooperative learning model are categorized as increasing with a percentage of low 21.74%, medium 13.04%, high 39.13% and very high 26.09%. The results of the descriptive statistical analysis using the t-test formula, it can be seen that the t-count value is 46.8 With a frequency (dk) of 23 - 1 = 22, at a significant level of 5%, t-Table = 2.07 is obtained. Therefore, it can be concluded that the null hypothesis (H0) is rejected and the alternative hypothesis (H1) is accepted, which means that there is an influence of the jigsaw cooperative learning model on learning outcomes in the social studies subject of grade V students of SD Negeri Sudirman IV Makassar.